Cycle-oriented distributed preconfiguration: ring-like speed with mesh-like capacity for self-planning network restoration - Grover, W.D.; Stamatelakis, D. (1998 IEEE International Conference on Communications, 1998)
Cycle-oriented preconfiguration of spare capacity is a new idea for the design and operation of mesh-restorable networks. It offers a sought-after goal: to retain the capacity-efficiency of a mesh-restorable network, while approaching the speed of line-switched self-healing rings. We show that through a strategy of pre-failure cross-connection between the spare links of a mesh network, it is possible to achieve 100% restoration with little, if any, additional spare capacity than in a mesh network. In addition, we find that this strategy requires the operation of only two cross-connections per restoration path. Although spares are connected into cycles, the method is different than self-healing rings because each preconfigured cycle contributes to the restoration of more failure scenarios than can a ring. Additionally, two restoration paths may be obtained from each pre-formed cycle, whereas a ring only yields one restoration path for each failure it addresses. We give an optimal design formulation and results for preconfiguration of spare capacity and describe a distributed self-organizing protocol through which a network can continually approximate the optimal preconfiguration state.